The Effect Of Workload On Nurses' Mental Health At Duren Sawit Drug Surgery, East Jakarta - Arif Rahman; Mahyar Suara; Achmad Fauzi (Jurnal Ners, 2026)
Background: Nurses are among the healthcare workers who play a crucial role in the healthcare system. High workloads, long hours, shift systems, and limited staffing often result in nurses having to handle excessive workloads. This can lead to physical exhaustion, emotional stress, and a reduced quality of life. The pressure of workload not only impacts the physical but also significantly impacts the mental health of nurses. Research Objective: To determine the influence of workload on the mental health of nurses. Research Method: This study used a cross-sectional analytical design. The sample in this study were some of the nurses working in Building A of the Duren Sawit Regional Specialist Hospital, East Jakarta, in November 2025, with a total sample size of 58 people. The sampling technique used was random sampling. Research Results: The majority of respondents were aged 26-35 years (72.4%), had a Diploma III in Nursing (84.5%), were female (58.6%), had mild/moderate disorders (70.7%), and had a heavy workload (48.3%). There was an effect of workload on nurses' mental health, with a p-value of 0.002. Conclusions and Recommendations: Workload impacts nurses' mental health. Nurses are expected to improve their stress management skills, maintain a balance between work and personal life, and utilize available mental health support facilities.